Molecular Response in Intestinal and Immune Tissues to in Ovo Administration of Inulin and the Combination of Inulin and Lactobacillus lactis Subsp. cremoris - Dunislawska, Aleksandra; Herosimczyk, Agnieszka; Lepczynski, Adam; Slama, Petr; Slawinska, Anna; Bednarczyk, Marek; Siwek, Maria (Frontiers in Veterinary Science, 2021)
Intestinal microbiota are a key factor in maintaining good health and production results in chickens. They play an important role in the stimulation of immune responses, as well as in metabolic processes and nutrient digestion. Bioactive substances such as prebiotics, probiotics, or a combination of the two (synbiotic) can effectively stimulate intestinal microbiota and therefore replace antibiotic growth promoters. Intestinal microbiota might be stimulated at the early stage of embryo development in ovo. The aim of the study was to analyze the expression of genes related to energy metabolism and immune response after the administration of inulin and a synbiotic, in which lactic acid bacteria were combined with inulin in the intestines and immune tissues of chicken broilers. The experiment was performed on male broiler chickens. Eggs were incubated for 21 days in a commercial hatchery. On day 12 of egg incubation, inulin as a prebiotic and inulin with Lactobacillus lactis subsp. cremoris as a synbiotic were delivered to the egg chamber. The control group was injected with physiological saline. On day 35 post-hatching, birds from each group were randomly selected and sacrificed. Tissues (spleen, cecal tonsils, and large intestine) were collected and intended for RNA isolation. The gene panel (ABCG8, HNF4A, ACOX2, APBB1IP, BRSK2, APOA1, and IRS2) was selected based on the microarray dataset and biological functions of genes related to the energy metabolism and immune responses. Isolated RNA was analyzed using the RT-qPCR method, and the relative gene expression was calculated. In our experiment, distinct effects of prebiotics and synbiotics following in ovo delivery were manifested in all analyzed tissues, with the lowest number of genes with altered expression shown in the large intestines of broilers. The results demonstrated that prebiotics or synbiotics provide a potent stimulation of gene expression in the spleen and cecal tonsils of broiler chickens. The overall number of gene expression levels and the magnitude of their changes in the spleen and cecal tonsils were higher in the group of synbiotic chickens compared to the prebiotic group.